1998
DOI: 10.1016/s0191-8869(97)00207-9
|View full text |Cite
|
Sign up to set email alerts
|

The Frost Multidimensional Perfectionism Scale revisited: More perfect with four (instead of six) dimensions

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
160
3
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(190 citation statements)
references
References 33 publications
19
160
3
8
Order By: Relevance
“…The six component solution explained 61.02% of the total scale variance. All of the factors had good psychometric properties (Cronbach α F1 = .933; F2 = .829; The four factor solution was similar to the structure found by other autors [15][16][17][18]26 showing an aggregation of the CM and DA dimensions and of the PE and PC dimensions. These lead to two new subscales: CMDA and PEPC.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The six component solution explained 61.02% of the total scale variance. All of the factors had good psychometric properties (Cronbach α F1 = .933; F2 = .829; The four factor solution was similar to the structure found by other autors [15][16][17][18]26 showing an aggregation of the CM and DA dimensions and of the PE and PC dimensions. These lead to two new subscales: CMDA and PEPC.…”
Section: Discussionsupporting
confidence: 67%
“…The original version of FMPS 1 presents six dimensions, but this factor structure was not always replicated. Purdon et al 14 found a three factor solution in a sample of anxiety disorders, and other researchers found four factor solutions [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 97%
“…Factor analytic studies investigating the dimensionality of Frost et al's model, however, consistently found fewer than six dimensions (Purdon, Antony, & Swinson, 1999;Cox, Enns, & Clara, 2002) with the majority of studies suggesting that four dimensions-combining concern over mistakes and doubts about actions to one dimension, and parental expectations and parental criticism to one dimension-best capture the dimensionality of the model (Harvey, Pallant, & Harvey, 2004;Stöber, 1998;.…”
Section: Multidimensional Perfectionismmentioning
confidence: 99%
“…However, there are single scales that represent proxy measures of the two dimensions. Regarding the perfectionistic strivings dimension, proxy measures are the FMPS Personal Standards scale, particularly when only the items measuring pure personal standards are regarded (DiBartolo, Frost, Chang, LaSota, & Grills, 2004); the MPS Self-Oriented Perfectionism scale, particularly when only the items measuring perfectionistic striving are regarded (Campbell & Di Paula, 2002;Stoeber & Childs, 2010) (Stöber, 1998;Stumpf & Parker, 2000); the MPS Socially Prescribed Perfectionism scale, particularly when the items measuring conditional acceptance are regarded (Campbell & Di Paula, 2002;Stoeber & Childs, 2010); the APS-R Discrepancy scale; the PI Concern over Mistakes scale; the Sport-MPS Concern over Mistakes scale; the MIPS Negative Reactions to Imperfection scale; and the MPCI Concern over Mistakes scale.…”
Section: Measures [H2]mentioning
confidence: 99%